Implementation of Street Vendor Arrangement Policy in Sidoarjo Regency - Muhammad Abdur Rozaq; Isnaini Rodiyah (Universitas Muhammadiyah Sidoarjo, 2022)
The purpose of this study is to analyze the structuring policy of street vendors as well as the factors that inhibit and support the implementation of street vendor policies. This study refers to the theory of George C. Edwards III, namely: communication, resources, disposition, and bureaucratic structure. This research method is a qualitative method with a technique of determining informants, namely purposive sampling. Data collection techniques using observation, interviews, and documents. The data analysis uses Miles and Hubberman analysis, namely data reduction, presentation and conclusion. Based on the results of this study, it is stated that the implementation of the policy of structuring street vendors in Gading Fajar, Sidoarjo Regency in terms of communication has been carried out well in a persuasive and repressive manner to Gading Fajar PKL, Sidoarjo Regency, the human resources of the policy implementing apparatus are adequate, the budget resources are adequate. obtained is in accordance with what is determined through the APBD. The authority resources of each government agency Disperindag and Satpol PP have carried out their duties and authorities. Facilities resources that support agencies in implementing the policy on structuring street vendors in Gading Fajar have been fulfilled while facilities for street vendors such as a permanent place for PKL Gading Fajar are not yet available, the disposition of the Disperindag and Satpol PP are committed to implementing the policy for structuring street vendors in Gading Fajar. Sidoarjo Regency in accordance with the existing rules, the SOP bureaucracy structure has been implemented in accordance with the existing rules. The supporting and inhibiting factors for the implementation of street vendor structuring policies in Gading Fajar, Sidoarjo Regency are supporting factors: the role of the Sidoarjo Regency Government, Budget Resources, Effective Policy Socialization, and the active role of street vendors. Inhibiting Factors of Land Availability and Lack of Awareness of Street Vendors